Multimedia Interaktif Macromedia Flash pada Materi Keragaman Budaya Indonesia di Sekolah Dasar - Laksana Wahyu Cahyaningsih; Dewi Nilam Tyas (Jurnal Pendidikan dan Pengajaran, 2024)
The main obstacle underlying this research is the need for teachers to use a greater variety of digital media in teaching science subjects. This research aims to develop interactive Macromedia Flash multimedia, test the feasibility of developing Macromedia Flash interactive multimedia, and test the effectiveness of Macromedia Flash interactive multimedia in improving student learning outcomes on material about Indonesian cultural diversity. The type of research used is included in the R&D (Research and Development) research category using the Borg and Gall model. The subjects in this research were an expert in the field of media, an expert in the field of learning materials, a teacher, and 23 students in class IV elementary school. Data were collected through observation, interviews, documentation, questionnaires, and written tests. The research instrument is a questionnaire sheet with test questions. The data analysis techniques used are descriptive, quantitative, qualitative, and inferential statistics. The research results, namely the media and material experts' feasibility results, were classified as "very feasible." The t-test (paired sample t-test) effectiveness test shows a significant difference between the pre-test and post-test scores. The N-gain results show that the N-gain value is 0.60, which is in the "moderate" improvement category. It was concluded that interactive multimedia (Macromedia Flash) can improve science learning for elementary school students. The implication of this research is that the interactive macromedia flash multimedia that has been developed can be used in learning, especially regarding Indonesian cultural diversity material in elementary schools.